Punishment sensitivity and the persistence of anorexia nervosa: High punishment sensitivity is related to a less favorable course of anorexia nervosa. Issue 5 (29th March 2022) - Jonker, Nienke C.; Glashouwer, Klaske A.; de Jong, Peter J.
Abstract: Objective: Cross‐sectional research provides robust evidence that individuals with anorexia nervosa (AN) report higher punishment sensitivity (PS) than individuals without an eating disorder (ED). High PS might interfere with treatment motivation and the ability to learn from experience. The current study took a longitudinal approach to test predictions that follow from the proposed relevance of PS as a factor in the persistence of AN symptoms. More specifically we tested (1) if higher PS at the start of treatment was related to less improvement in ED symptoms after one year, and (2) if a decrease in ED symptoms was associated with a concurrent decrease in PS. Method: Participants were 69 adolescents with a diagnosis of AN at the start of treatment of whom 62 participated again one year later. ED symptom severity and PS were assessed at both time points. Results: Findings showed that (1) higher PS at the start of treatment was related to less improvement in ED symptoms, and (2) an improvement in ED symptoms was related to a decrease in PS. Discussion: These findings are consistent with the proposed relevance of PS in the persistence of AN and suggest that it might be beneficial to address high PS in treatment. Public Significance: Consistent with the view that punishment sensitivity (PS) is related to the persistence of anorexia nervosa, high PS at the start of treatment was related to less improvement in eating disorder symptoms in patients with anorexia nervosa. Furthermore, an improvement in eating disorder symptoms was associated with a concurrent decrease in PS, suggesting that PS can be subject to change and may be a relevant target for treatment.